North Korean foreign policy : security dilemma and succession - Kim, Yong-ho, 1964- (Lexington Books, 2011)
North Korean Foreign Policy: Security Dilemma and Succession, by Yongho Kim, starts from the point of view that North Korea's provocations have been motivated more by fear than by her in-born provocative nature. Kim argues that North Korea's provocative foreign policy reflects its threat perception stemming from various security dilemma, and a very real concern regarding another father-to-son succession. This volume views North Korea's external and domestic threats as causes and its provocative foreign policy as an effect of the causes. The security dilemma has impelled North Korea to generate.